Use of Mythical Creatures in Folk Literature of Southeast Asia: A Comparative analysis - Edgar R. Eslit (IJRAEL: International Journal of Religion Education and Law, 2023)
This paper presents a comparative analysis of the use of mythical creatures in Southeast Asian folk literature, focusing on the dragons in Javanese folktales from Indonesia, the naga in Thai folklore, and the aswang in Filipino mythology. The paper examines the historical and cultural context of Southeast Asia, the evolution of folk literature in the region, and the role of mythical creatures in Southeast Asian culture. It analyzes the similarities and differences in the portrayal of mythical creatures across different cultures, identifies common themes and motifs in Southeast Asian folk literature, and evaluates the significance of the use of mythical creatures in conveying cultural values and beliefs. The paper concludes that the use of mythical creatures is an important aspect of Southeast Asian folk literature and highlights the implications of the study for future research in the field. The findings contribute to a deeper understanding of the cultural and historical heritage of Southeast Asia and shed light on the unique features of its folk literature.